A systematic literature review of multi-criteria analysis model methods on sustainability weighting for ethanol plant - Norfazilah, Abdul Halim; Nor Zalina, Kasim; Aliff Radzuan, Mohamad Radzi; Faiz, Mohd Turan (Akademi Sains Malaysia, 2021)
The sustainability weighting is crucial as it is practically implemented into sustainability evaluation, especially in industrial development. Sustainability is about the interconnection between three aspects of sustainability impact such as economic impact, environmental impact, and social impact. Multi-Criteria Analysis (MCA) model play important roles to measure the weighting for each impact according to the scenario and criteria selected based on scientific rules and robust statistical methods. However, there were insufficient studies on the existing literature sustainability weighting model from MCA method for the ethanol plant. Hence, the present paper demonstrates a systematic literature review of MCA model methods on sustainability weighting for the ethanol plant. There are two steps involved in systematic literature reviews: formulation of the research question and systematic searching strategies consisting of identification, screening, eligibility, quality appraisal, data abstraction and analysis. The review is based on leading databases; Scopus – ScienceDirect, Springer, Taylor and Francis, and one supporting database – Google Scholar. From the review, the preferable MCA weighting model for sustainability evaluation of ethanol plants is ‘integrated Analytical Hierarchy Process (AHP)’ rather than ‘standalone AHP’. The paper offered a significant contribution to the body of knowledge and sustainability evaluation purposes.